Barix multilayer barrier technology for organic solar cells - Moro, Lorenza; Rutherford, Nicole M.; Visser, Robert Jan; Hauch, Jens A.; Klepek, Claudia; Denk, Patrick; Schilinsky, Pavel; Brabec, Christoph (Proc. of SPIE Vol. 6334, 2006)
The effect of multilayer barrier materials on the lifetime of organic photovoltaic cells has been investigated. For thin film encapsulated cells a protective layer was used to prevent damage during barrier layer deposition. No post deposition effects developed after dry box storage. In accelerated temperature and humidity lifetime testing the degradation of the encapsulated cells can be related to the loss of effective cell area. An extrapolation of the lifetime at room conditions has been quantitatively determined by comparing the cell degradation with the loss of Ca in a Caoxidation test. The results indicate a barrier permeation rate of 10 gr /[m* day] for these samples, corresponding to a lifetime of greater than 5000 hours. Routes to improvement of the OPV cell lifetime are discussed.
Keywords: Barrier films; Barrier layers; Bulk heterojunction; Conjugated polymers; Degradation; Encapsulation; Organic solar cells